Genetic Etiologies in Developmental and/or Epileptic Encephalopathy With Electrical Status Epilepticus During Sleep: Cohort Study - Gong, Pan; Xue, Jiao; Jiao, Xianru; Zhang, Yuehua; Yang, Zhixian (Frontiers in Genetics, 2021)
Background: Recently, the electroencephalogram (EEG) pattern of electrical status epilepticus during sleep (ESES) had been reported in some genetic disorders and most of them were noted with developmental and epileptic encephalopathy (DEE) or epileptic encephalopathy (EE). This study aimed to determine the genetic etiologies and clinical characteristics of ESES in DEE/EE. Methods: We performed a cohort study in cases of developmental and epileptic encephalopathy (DEE) or epileptic encephalopathy (EE) with ESES. Tio-based genetic testing was performed in 74 cases and was analyzed to identify underlying variants. Results: Pathogenic or likely pathogenic variants were identified in 17/74 cases, including KCNQ2 (n=6), KCNA2 (n=5), GRIN2A (n=3), SLC9A6 (n=1), HIVEP2 (n=1), and RARS2 (n=1). Eleven were boys. The median age at seizure onset was 6 months. ESES occurred at the mean age of 2.0 ± 1.2 years, predominant in Rolandic region in 14. Twelve of 17 cases had a first stage of different epilepsy preceding ESES, and 2/12 were diagnosed as Ohtahara syndrome, 2/12 as infantile spasms, 3 as DEE and 5/12 as EE without epileptic syndrome. Conclusion: Monogenic variants explained over 20% of DEE/EE with ESES. ESES could be an age-related feature in genetic disorders and occurred following the first stage of different epilepsy. Both age-related factors and genetic etiology were suggested to play a role in the occurrence of ESES in genetic DEE/EE.